2021
DOI: 10.1002/eat.23639
|View full text |Cite
|
Sign up to set email alerts
|

Parent strategies for expanding food variety: Reflections of 19,239 adults with symptoms of Avoidant/Restrictive Food Intake Disorder

Abstract: Objective To characterize helpful parent feeding strategies using reflections on childhood eating experiences of adults with symptoms of Avoidant/Restrictive Food Intake Disorder (ARFID). Method We explored a unique text‐based dataset gathered from a population of N = 19,239 self‐identified adult “picky eaters.” The sample included adults with symptoms of ARFID as evidenced by marked interference in psychosocial functioning, weight loss/sustained low weight, and/or nutritional deficiency (likely ARFID), and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The ndings from this study highlighted the importance of families being able to accept the diagnosis in order to be able to divert their focus towards supporting their child with ARFID with their eating behaviours. Research shows the encouragement for parents to continually support their child with ARFID using feeding strategies, albeit continuing to observe some degree of food avoidance [31]. This signi es the value of families, where the knowledge and training of support for the child is abundant.…”
Section: Encountering the Arfid Diagnosismentioning
confidence: 98%
See 2 more Smart Citations
“…The ndings from this study highlighted the importance of families being able to accept the diagnosis in order to be able to divert their focus towards supporting their child with ARFID with their eating behaviours. Research shows the encouragement for parents to continually support their child with ARFID using feeding strategies, albeit continuing to observe some degree of food avoidance [31]. This signi es the value of families, where the knowledge and training of support for the child is abundant.…”
Section: Encountering the Arfid Diagnosismentioning
confidence: 98%
“…The study by Rogers et al (2012) strongly reiterates the negative feelings of parents, especially mothers, as they worry about the health consequences of their child with feeding di culties. Despite this, parents try hard to maintain a positive atmosphere around the individual with ARFID, where research has shown an optimistic perspective around food intake could possibly aid in improving their feeding behaviours [31]. Studies have also shown the family value in support for individuals with ARFID, especially during interventions where parents could independently support their child at home [30].…”
Section: Encountering Arfid Diagnosismentioning
confidence: 99%
See 1 more Smart Citation